Pengabdian Tanggap Bencana Distribusi Logistik di Desa Sekip, Kecamatan Lubuk Pakam, Kabupaten Deli Serdang, Provinsi Sumatera Utara - Rini Indahwati; Nurhaflah Soraya; Rahmadani; Muhammad Asrin Jazuli (JURPIKAT, 2026)
The heavy rainfall caused a flood in Deli Serdang Regency on November, 30th 2025. For responding to this disaster, the Higher Education, Science & Technology Ministry funded community services activities, especially logistics distribution for the society. Politeknik Negeri Medan is one of the higher education institutions in Sumatera Utara, acting as the mediator for the logistic distribution process. This community service aims to help the society that impacted by the flood and landslide in Desa Sekip, Kecamatan Lubuk Pakam, Kabupaten Deli Serdang, Provinsi Sumatera Utara.